Optimalisasi Supervisi Keperawatan dalam Implementasi Program Nasional Penanggulangan Tuberkulosis - Djarang, Lilyance; Hariyati, Rr Tutik Sri; Wildani, Andi Amalia; Asmara, Amelia; Aziz, Herawani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to encourage optimization of the implementation of nursing supervision for TB program activities in hospitals. The method used is a case report, which was carried out in one of the inpatient rooms at Hospital X. Data collection techniques were through observation, interviews and questionnaires. The total sample was 22 executive nurses. The results of the assessment are analyzed to determine the problem, determine interventions to solve the problem, and prepare a Plan of Action. The results of the survey showed that the planning function of the head of the ward was not optimal, as evidenced by the lack of nursing supervision regarding the implementation of the national tuberculosis program, namely education, recording and reporting as well as Infection Prevention and Control. Nursing supervision guidelines have been prepared and follow-up plans have been made for their implementation. In conclusion, the implementation of nursing supervision needs to be optimized, including nursing supervision of national Tuberculosis program activities, in order to ensure the quality of nursing care. Keywords: National Tuberculosis Program, Nursing supervision